Incidence of malignancy and the role of gastric biopsy in Patients with perforated gastric ulcer in Thailand. - Janwanitchsthaporn, Sorawat (Region 11 Medical Journal, 2018)
Background: Perforated gastric ulcer is one of the most common diseases that require emergency surgery. The main etiologyof perforation is benign ulcer but malignant ulcer is found in 6 – 14% of cases and difficult to be preoper¬atively diagnosed. Then routine gastric biopsy is recommended. But difference in behavior, characters, and etiology of gastric ulcer in Thai patient raise the question of the real incidence of gastric malignancy and the role of gastric biopsy in Thai patients. Objectives: To determine the incidence of gastric malignancy and to explore the associated risk factors in the patients with perforated gastric ulcer, and to assess the role of gastric biopsy in the patient with gastric ulcer perforation at Suratthani hospital, Thailand.Methods: A retrospective study was conducted by reviewing medical records from all 225 patients who were diagnosed of perforated gastric ulcer during January 1st, 2011 to December 30th, 2017 in Suratthani hospital. The 178 records which had sufficient data were enrolled into the study.Results: The incidence of malignancy in perforated gastric ulcer was 2.8% (5 of 178 patients). Two statistical significant factors that associated to malignancy were gross appearance of ulcer (OR 20.6, p<0.05) and the location of ulcer. The gross appearance of ulcer which associated to malignancy were chronic ulcer (8.8%, 3 of 34 patients) and mass like lesion (66%, 2 of 3 patients). None of 147 acute ulcers was malignancy. The ulcers that located at non-prepyloric area were significant associated to malignancy (OR 18.5, p<0.05).Conclusion: The incidence of malignancy in perforated gastric ulcer was very low in this study. Two statistical significant factors that associated to malignancy were gross appearance andlocation of ulcer. Gastric biopsy maybe not necessary in acute ulcer that located at pre-pyloric area